Didaktik informed teaching arrangements in preschool with a focus on movement - Jan-Eric Ekberg; Ann-Christine Vallberg Roth (Educare)
Most children attend preschools in Sweden, and preschool is thus an important arena for children’s development and growth as well as for the development of and through movement. However, little is known about the teaching of movement in Swedish preschools. This article develops knowledge of what can characterize such teaching, particularly regarding goal and motive, content, and teaching actions. The material was generated in 2018–2019 in collaboration with 42 preschool departments in Sweden. The theoretical approach is “didaktik”, and “why”, “what”, and “how” questions are used as analytical tools. A variety of content can be seen, such as fundamental movement skills, different aspects of movement and, in a few teaching arrangements, physical activity. The teaching is often led by the teacher, though the children are sometimes co-leaders. The results also indicate a focus on inherent values but also on investment and added values. The study highlights the importance of preschool teachers’ attention to the prospective object and purpose of teaching movement, but also of teachers’ competence and the need for conscious strategies for teaching movement. Through well-grounded didaktik choices, children can be offered good opportunities to experience and explore movement.